The influence of ethical leadership on academic employees' organizational citizenship behavior and turnover intention: Mediating role of intrinsic motivation. Issue 3 (21st August 2018) - Shareef, Raad Abdulkareem; Atan, Tarik
Abstract : Purpose: The purpose of this paper is to examine the effect of ethical leadership on followers' organizational citizenship behavior (OCB) and turnover intention and to examine the mediating role of intrinsic motivation in the relationships. Design/methodology/approach: The study employed a quantitative research method with a sample of 351 supervisor–subordinate dyads in three large public universities in the Kurdistan Region of Iraq. The statistical analysis was conducted using Statistical Package for Social Science software, through multiple regression analyses to test the research hypotheses. Findings: The results indicated that ethical leadership positively related to OCB and negatively related to turnover intentions. The results also showed that intrinsic motivation fully mediates the relationship between ethical leadership, OCB, and turnover intentions. Originality/value: This study recognized the gap in the literature, and it contributes to the body of knowledge through an examination of the mediating role of intrinsic motivation between ethical leadership, OCB and turnover intention, relying on the cognitive evaluation theory.